Leucorrhoea in Young Women and Determinants of Preventive Behavior : A Literature Review - Armini, Ni Ketut Alit; Lestari, Wahyuni Tri (Pediomaternal Nursing Journal, 2022)
Introduction: Vaginal discharge can occur in every woman anywhere in the world. Teenage girls are more at risk, though. It's still a challenge to get teenage females to keep their reproductive organs clean as one of their preventative measures against vaginal discharge. This literature review aims to understand the prevalence of vaginal discharge and the factors that influence adolescents' preventive behavior. Methods: The academic databases (Scopus, Proquest, Pubmed, and Garuda), which comprise works published in the 2016–2021 time frame, were searched for relevant articles using a combination of keywords. The framework for this investigation is PICOS. Articles were systematically chosen by reviewing their English and Indonesian, checking for duplication, examining titles and abstracts, determining whether they eligible for full-text reviews, and determining whether they were appropriate for the study's objectives. The study's participants were female teenagers. Results: Ten papers were discovered that satisfied the review's inclusion requirements. While some adolescent females experience vaginal discharge, others think it to be normal and unproblematic. In order to prevent vaginal discharge in adolescent girls, it is essential to have effective personal hygiene. Adolescents' personal hygiene practices are determined by their knowledge, attitudes, and support systems. Conculusion: Most young women are unaware of the serious effects vaginal discharge can have on reproductive health. To improve adolescent girls' understanding and health status, humanistic health promotion about the behavior of preventing vaginal discharge is still important.